Joint venture dissolution - Vennat, Michel (Revue générale de droit)

(untitled) (Éditions Wilson & Lafleur, inc., 1988)
Joint ventures invariably encounter with changes in circumstances and conditions that may either frustrate the original goals of the joint venturers or render the undertaking unprofitable or unmanageable. That is why there are no more important provisions of the joint venture agreements than those which govern its termination.Relating to those provisions, the author will refer to considerations that will apply whatever the form of the joint venture.